Fire Resistance of Composite Beams with Restrained Superposed Slabs - Junli Lyu; Qichao Chen; Huizhong Xue; Yongyuan Cai; Jingjing Lyu; Shengnan Zhou (Advances in Materials Science and Engineering)
To investigate the fire resistance of composite beams with restrained superposed slabs, three specimens were tested under uniformly distributed loads in a furnace. The effects of the thickness of the postcast top layer in superposed slabs and the spacing of shear studs on the structural behaviours of composite beams under fire were further examined. During the tests, the temperature distributions of the superposed slabs and steel beams as well as the displacements at their key positions were recorded and analysed. It was found that the temperature of the concrete superposed slabs decreased long their heights from the bottom. The most drastic change of the temperature along the slab cross section was found in the region with a distance of 40 mm to the slab bottom. The concrete superposed slabs could impose restraints to the steel beams due to their incompatible deformations. Cracks were developed on the top surfaces of the specimens and the superposing interfaces between the precast slabs and postcast top layers were not broken. Through the comparisons of different specimens, the spacing of shear studs could have a significant effect on the fire resistance of composite beams, especially for their deformation recovery capacities. In contrast, the effect of the thickness of the postcast top layers was negligible. ABAQUS was employed to simulate the temperature fields and deformation behaviours of composite beam specimens based on a sequenced thermomechanical coupling analysis. The numerical results agreed well with the experiment data, which validated the developed numerical model.